2010
DOI: 10.1126/science.1185100
|View full text |Cite
|
Sign up to set email alerts
|

Loss of Rap1 Induces Telomere Recombination in the Absence of NHEJ or a DNA Damage Signal

Abstract: Shelterin is an essential telomeric protein complex that prevents DNA damage signaling and DNA repair at mammalian chromosome ends. Here we report on the role of the TRF2-interacting factor Rap1, a conserved shelterin subunit of unknown function. We removed Rap1 from mouse telomeres either through gene deletion or by replacing TRF2 with a mutant that does not bind Rap1. Rap1 was dispensable for the essential functions of TRF2 – repression of ATM kinase signaling and non-homologous end-joining (NHEJ) – and mice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
265
1
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 250 publications
(289 citation statements)
references
References 26 publications
14
265
1
1
Order By: Relevance
“…138 Recent studies have shown that RAP1 specifically is critical for the HDR protection pathway. 139 In MEFs Ku70 -/-, both RAP1 knock-out and a RAP1 binding-deficient TRF2 allele showed an increase in T-SCE to 10-12% from a 2-3% baseline. 139 Preventing HDR at telomeres is extremely important as it can lead to unequal DNA exchange and rapid telomere loss with disastrous effects for the cell.…”
Section: Resultsmentioning
confidence: 99%
“…138 Recent studies have shown that RAP1 specifically is critical for the HDR protection pathway. 139 In MEFs Ku70 -/-, both RAP1 knock-out and a RAP1 binding-deficient TRF2 allele showed an increase in T-SCE to 10-12% from a 2-3% baseline. 139 Preventing HDR at telomeres is extremely important as it can lead to unequal DNA exchange and rapid telomere loss with disastrous effects for the cell.…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, the finding that very short telomeres without t-loops exist stably in vivo (47), that the TRF2-Rap1 complex can prevent NHEJ of telomeres with less than 10 repeats and in the absence of Rap1, can only be compensated by significantly high amounts of hTRF2 to facilitate end protection (12,48) provide support to this model. Depending on what parameter one measures, the loss of Rap1 in cells may be considered to be important for end protection or not (12,28). This illustrates importance of further work that will better link end protection in vivo with the physical complexes and structures formed at telomere by the shelterin.…”
Section: Discussionmentioning
confidence: 99%
“…hRap1 regulates the expression level of genes that are in close proximity to its binding sites and regulates telomere length through its BRCT domain (11,26). Moreover, Rap1 alone suppresses NHEJ in human extracts and homologous recombination in mouse cells (23,28). However, significantly less is known about the function and role of Rap1 in human or mouse cells in the suppression of the DNA damage response.…”
mentioning
confidence: 96%
“…1,2 Rap1 protects telomeres against recombination and reduces their fragility by repressing homology-directed repair and preventing sister chromatid exchange. [3][4][5] Besides the maintenance of telomere integrity, Rap1 also regulates gene transcription by binding to non-telomeric sites. 4 It regulates genes involved in insulin secretion, peroxisome proliferator-activated receptor (PPAR) signaling and growth hormone pathways.…”
Section: Introductionmentioning
confidence: 99%